Library utilization and satisfaction of high school teachers in international schools in Metro Manila - Burgos, Czaremma April A. (School of Library and Information Studies, University of the Philippines, Diliman, 2018)
The aim of this study was no investigate the utilization of existing resources and services of the libraries of selected international school in Metro Manila. There are five international schools included in the study and 80 high school teachers were surveyed to determine their rates of expectation and satisfaction toward the library services and products.